Case report: Successful treatment of hyperkalemia during general anesthesia in a domestic cat - Irizarry, Tiffany; Gradilla, Sarah (Frontiers in Veterinary Science, 2024)
ABSTRACT Objective To describe the successful identification and treatment of severe hyperkalemia, cardiac arrhythmia, rhabdomyolysis, and acute kidney injury (AKI) in a domestic cat that underwent general anesthesia for abdominal exploratory surgery. The definitive underlying cause remains unknown; however, a propofol reaction is suspected. Case Summary A 6-month-old male, intact, domestic short-hair cat underwent general anesthesia and developed severe intraoperative rhabdomyolysis, hyperkalemia, ventricular fibrillation, and AKI during surgery despite documented mild hypokalemia and normal creatinine prior to induction of anesthesia. Propofol was administered as part of the anesthetic protocol. The patient was resuscitated successfully and responded well to advanced medical intervention. The hyperkalemia and AKI resolved within less than 24 hours from surgery and rhabdomyolysis was resolved at the time of recheck 5 days later. New or Unique Information Provided While previously suspected in dogs, to the authors’ knowledge, propofol-related infusion syndrome (PRIS) has not been reported in domestic cats. Veterinary professionals should be aware that drug-induced intraoperative rhabdomyolysis and hyperkalemia can develop unexpectedly and should remain a differential for acute cardiac arrhythmias or cardiac arrest and AKI. KEYWORDS CPR, propofol-related infusion syndrome, hyperkalemia, creatine kinase, case report Abbreviation AKI, acute kidney injury; CK, creatine kinase; CPR, cardiac and pulmonary resuscitation; ECG, electrocardiogram; LRS, Lactated Ringer’s solution; MAP, mean arterial pressure; MGCS, Modified Glasgow Coma Scale; TAP, transversus abdominus plane; PLR, pupillary light reflex; PRIS, propofol-related infusion syndrome